MODERNETIOLOGICAND GENDER FEATURESOFMICROBAL SPECTRUMOFURINE IN TEENAGERS WITH URINARYTRACTINFECTIONS - V.V. Bezruk; T.O. Bezruk; O.V. Blinder (Український Журнал Нефрології та Діалізу, 2014)
In Ukraine the increase of amount of teenagers registers with the infection of the urinary system.